تمثلات استخدام الذكاء الاصطناعي في التحصيل الاكاديمي لدى الطلبة الجامعيين - حرارة دنيا; دحمان فاطمة الزهرة (جامعة الوادي University of Eloued, 2026)
"الملخص : تهدف هذه الدراسة إلى التعرف على تمثلات وتصورات الطلبة الجامعيين لإستخدام الذكاء الإصطناعي في عملية التحصيل الأكاديمي ، من خلال آرائهم ، وفهم تصوراتهم، وحتى تجاربهم الشخصية في حد ذاتها في توظيف هذه التقنية في السياق التعليمي. وتسعى دراستها إلى رصد أثر التمثلات على مستوى التحصيل العلمي لدى الطلبة، وما مدى وعيهم وما إيجابيات وسلبيات الذكاء الإصطناعي في المسار الأكاديمي. إعتمادنا في هذه الدراسة على المنهج الوصفي ، مستخدمين أداة الإستبيان لجمع البيانات من العينة المكونة من 90 طالب وطالبة فقط، تخصص سمعي بصري سنة ثانية ماستر بكلية العلوم الإنسانية والإجتماعية. وقد تم تحليل البيانات والكشف عن إنعكاسات الذكاء الإصطناعي على التحصيل الأكاديمي. وأظهرت نتائج دراستنا أن أغلب الطلبة لديهم تصور إيجابي تجاه إستخدام تطبيقات وتقنيات الذكاء الإصطناعي، حيث يرون أنه يساهم وبشكل كبير في الوصول إلى المعرفة، وتنظيم المحتوى الدراسي ، وإنجاز الأعمال والتحضير للإمتحانات في وقت قصير ، وفي المقابل عبر بعض الطلبة على تخوفهم من الإعتماد المفرط عليه لما يسببه من ضعف في تنمية المهارات الشخصية." "Abstract: This study aims to explore university students’ representations and perceptions regarding the use of artificial intelligence (AI) in the process of academic achievement. It investigates their opinions, understanding, and even personal experiences with employing this technology in educational contexts. The study seeks to identify the impact of these representations on students’ academic performance, their level of awareness, as well as the perceived advantages and disadvantages of AI in academic pathways. A descriptive method was adopted in this study, using a questionnaire as the primary data collection tool. The sample consisted of 90 students specializing in Audiovisual Communication, in their second year of Master's studies at the Faculty of Humanities and Social Sciences. The collected data was analyzed to uncover the implications of AI on academic performance. The results of the study showed that most students hold a positive perception of using AI applications and technologies, considering them highly beneficial in accessing knowledge, organizing academic content, completing assignments, and preparing for exams in a short amount of time. However, some students expressed concern about excessive reliance on AI, fearing it may hinder the development of personal skills."
مذكرة ماستر قسم اعلام واتصال تخصص سمعي بصري
Keywords: الطالب الجامعي; التحصيل الاكاديمي; الذكاء الاصطناعي; Artificial intelligence; academic achievement; University student